ANALISIS UPAYA PAJAK, EFEKTIVITAS, DAN KONTRIBUSI PAJAK DAERAH DI KAWASAN EKONOMI KHUSUS PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KOTA BITUNG - Karo, Lusinda Natalya Debora; Kalangi, Lintje; Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2019)
Regional autonomy is a law that requires local governments to take care of their own regional needs by utilizing and exploring every potential that exists. One source of regional income is local tax. Local tax is fees paid by society to the state from results of natural resource management and other potential uses for people's welfare. The purpose of this study was to find out about tax effort, effectiveness, contribution and growth of local taxes in the City of Bitung. The research method used is descriptive qualitative. The results of this study indicate that tax efforts by the regional government of Bitung city in 2014-2018 are still in the criteria of